2012
DOI: 10.1097/mat.0b013e318260c6a6
|View full text |Cite
|
Sign up to set email alerts
|

Are Blood Stream Infections Associated With an Increased Risk of Hemorrhagic Stroke in Patients With a Left Ventricular Assist Device?

Abstract: Blood stream infections (BSIs) are an important cause of morbidity and mortality in patients with left ventricular assist devices (LVADs). The aim of this study was to examine the correlation between hemorrhagic cerebrovascular accident (CVA) and BSI after implantation of LVAD for advanced heart failure (HF). This was a retrospective descriptive review of 87 patients with end-stage HF, who underwent implantation of HeartMate II continuous-flow LVAD over a 4 year period. Blood stream infections were diagnosed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 29 publications
0
48
0
Order By: Relevance
“…The association that we found at our center between an increased risk of stroke and a history of sepsis has also been found in smaller previous studies as well, but it needs to be further examined. Infection or a proinflammatory state can contribute to systemic hypercoagulation, leading to potential thrombus formation and ischemic stroke [22]. A previous study has shown an asymmetry of stroke distribution, with rightsided strokes being more prevalent in LVAD patients, especially in patients with infections.…”
Section: Commentmentioning
confidence: 96%
“…The association that we found at our center between an increased risk of stroke and a history of sepsis has also been found in smaller previous studies as well, but it needs to be further examined. Infection or a proinflammatory state can contribute to systemic hypercoagulation, leading to potential thrombus formation and ischemic stroke [22]. A previous study has shown an asymmetry of stroke distribution, with rightsided strokes being more prevalent in LVAD patients, especially in patients with infections.…”
Section: Commentmentioning
confidence: 96%
“…In addition, the greater the amount of time supported by a CF-LVAD, the greater the risk of developing a PSI. 6 Several studies have reported an association between infection and cerebrovascular events (CVEs) in patients supported with LVADs, [7][8] and we recently reported that persistence of bacteremia greater than 72 hours is a crucial distinguishing factor. 9 We recently reported a 7-fold increase in CVEs in patients with HeartMate-II (HMII) devices who have persistent Pseudomonas aeruginosa bloodstream infections.…”
Section: Complications Of Infectionmentioning
confidence: 99%
“…13,14 Most of these studies included patients with both continuous-flow LVADs (CF-LVADs) and pulsatile-flow devices, thus limiting the extrapolation of these studies to contemporary LVAD usage, because CF-LVADs comprise O95% of current implantations. Patients with CF-LVADs have lower rates of both infection and CVA compared with patients who receive pulsatileflow LVADs.…”
mentioning
confidence: 99%
“…A recent pilot study found an association between CVA and any BSI in patients supported with Heartmate II (HMII; Thoratec Corp, Pleasanton, California) LVADs. 13 We conducted a retrospective study to explore these observations further with the specific aim to determine if persistent BSI (as opposed to transient BSI) is associated with an increased risk of all-cause CVA (hemorrhagic and/or ischemic) and all-cause mortality in patients who underwent HMII implantation at our institution.…”
mentioning
confidence: 99%